Study of Longitudinal Aging in Mice: Presentation of Experimental Techniques. (18th December 2020) - Palliyaguru, Dushani L; Vieira Ligo Teixeira, Camila; Duregon, Eleonora; di Germanio, Clara; Alfaras, Irene; Mitchell, Sarah J; Navas-Enamorado, Ignacio; Shiroma, Eric J; Studenski, Stephanie; Bernier, Michel; Camandola, Simonetta; Price, Nathan L; et al.
Abstract: Aging is associated with functional and metabolic decline and is a risk factor for all noncommunicable diseases. Even though mice are routinely used for modeling human aging and aging-related conditions, no comprehensive assessment to date has been conducted on normative mouse aging. To address this gap, the Study of Longitudinal Aging in Mice (SLAM) was designed and implemented by the National Institute on Aging (NIA/NIH) as the mouse counterpart to the Baltimore Longitudinal Study of Aging (BLSA). In this manuscript, we describe the premise, study design, methodologies, and technologies currently employed in SLAM. We also discuss current and future study directions. In this large population mouse study, inbred C57BL/6J and outbred UM-HET3 mice of both sexes are longitudinally evaluated for functional, phenotypic, and biological health, and collection of biospecimens is conducted throughout their life span. Within the longitudinal cohorts, a cross-sectional arm of the study has also been implemented for the well-controlled collection of tissues to generate a biorepository. SLAM and studies stemming from SLAM seek to identify and characterize phenotypic and biological predictors of mouse aging and age-associated conditions, examine the degrees of functional and biomolecular variability that occur within inbred and genetically heterogeneous mouse populations with age, and assess whether these changes are consistent with alterations observed in human aging in BLSA. The findings from these studies will be critical for evaluating the utility of mouse models for studying different aspects of aging, both in terms of interpreting prior findings and designing and implementing future studies.